Neuroparenting in Muslim and Catholic Children's Interactions at Dulur Ulin Festival - Andini, Andini; Siswanto, Mikael Adi; Rosyad, Rifki (Jurnal Iman dan Spiritualitas, 2025)
Encounters between religious communities are the gateway to knowing, understanding and tolerance. This was done by Catholic children from Joy Kids International Tasikmalaya Elementary School who visited the Darussalam Ciamis Islamic Boarding School. This encounter is packaged through the "Dulur Ulin" (Playmates) Festival. It is hoped that through this activity, children can find interfaith playmates. This encounter then becomes a new parenting model regarding the introduction of diversity of beliefs for parents and children. Because of the memory of encounters with different cultures and religions. Children can explore various cultures, cultures and religions through this festival. This article uses qualitative methods and a phenomenological approach to see to what extent this activity provides meaning for parents and children to see that the memory of fraternal encounters between religious communities can have an impact on thought patterns and attitudes for parents and children. So the analysis used is Neuroparenting, because the "Dulur Ulin" festival activities are expected to become a parenting program, namely introducing children to a diversity of beliefs. As a result, through meeting activities using traditional Sundanese games, children were able to establish communication, socialize and even explore good friends from Catholics and Muslims. The impression of happiness when playing with friends provides positive memories in seeing that differences in culture, culture and religion can still unite them in the game. So the "Dulur Ulin" festival can be used as a means of meeting between religious communities to build a memory of brotherhood for children.